ANALISIS KESALAHAN MAHASISWA SEMESTER II PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS DALAM MMENGGUNAKAN KATA KERJA BANTU DALAM MENULIS DI UNIVERSITAS KHAIRUN - Saiful Latif (Universitas Khairun, 2015)
This study aims to (1) get the types of grammatical (auxiliary) errors in non-fiction text writing among the second semester students of the English Education Department of Khairun University in the academic year of 2013/2014, and (2) get the sources of grammatical (auxiliary) errors in writing at the second semester students of the English Education Department of Khairun University in the academic year 2013/2014. The design of this research was qualitative research using the descriptive qualitative approach. The participants consisted of 12 students The main data were obtained from the 12 students’ compositions and the other data were collected from interviews. The results of the research show that (1) the students make errors in omission, addition, and misformation of be (be, am, is, are, was, were, beeb), do (do, does), have (have, has, had) and modals (can, must, will). (2) The source of error is intralingual errors and interlingual error. (3) The students also make error in using verbs after modal auxiliary. It means that the students still lack in mastering auxiliary verbs. Key word: Error Analysis, auxiliary verbs